Academic writing support : empowering undergraduates' academic writing / Siti Ruqayyah As-Sadiq Abdul Rahim - Abdul Rahim, Siti Ruqayyah As-Sadiq (2013)
Academic writing skills needs differ from one discipline to another. This is reflected in the nature of academic writing of the discipline, the academic writing challenges writers face and the resources that are available. In seeking to develop an empowered writer, the right provision of support should be made available according to the needs of the writer. This study investigates the academic writing needs and the academic writing support needs of undergraduates from three various discipline (TESL, Art and Science) of one faculty of Education at a public university in Malaysia. This is the only university with a language policy where English is the medium of teaching and learning. This study applies the mix method design of Plowright (2011), the Frameworks for an Integrated Methodology (FRalM). This study reports the findings of numerical data analysis generated from third year undergraduate students (n=196) and narrative data analysis from both academicians (n=4) and students (n=8). Findings indicated that there is an absence of academic writing support. The findings inform that although all three program disciplines are under the same faculty, their academic writing needs are distinctively different. This study proposes that an academic writing support in the form of a writing centre would be able to facilitate the varying academic writing needs of undergraduates in the faculty.